Does Investment, Zakat, Infak And Shadaqah And Inflation Infuence The Economic Growth?: Evidence From Indonesia - Andi Triyawan; Siska Arie Novita; Nursilah Ahmad; Noradilah Abdul Hadi; Asmaddy Haris (Institut Agama Islam (IAI) Al-Qolam, 2024)
Volume: 7 No:1 (page: 8-19)